Building loyalty through satisfaction: Costa coffee self service vending machine - Lim, Zhi Qian (2023)
The purpose of this empirical study is to investigate the satisfaction and loyalty of customers towards the use of Costa Coffee Self Service Vending Machine. In this research, questionnaires were adapted and the data of 300 respondents have been collected. However, after filtering, only 250 set of questionnaires are qualified to conduct the research. Data analysis was done by using SPSS software. The results from this research shown that most of the variables significant with satisfaction and loyalty, but only one independent variable namely convenience (C) does not have significant relationship on satisfaction loyalty towards the Costa Coffee Self Service Vending Machine. The results proved that convenience (C) does not indirectly affect the loyalty towards Costa Coffee Self Service Vending Machine even there is a presence of mediator variable (Satisfaction). This study makes a valuable reference contribution to the current literature on coffee retailers and also marketing teams especially for Costa Coffee by performing a set of symmetric analysis methods to assess Costa coffee lovers’s expectations and responses.